Reflux esophagitis. Hiatal hernia - Cendán Alfonzo, Juan E (Cirugía del Uruguay, 2020)
Reflux esophagitis is a serious complication that requires the greatest preoccupation of the surgeon for prophilaxis and surgical treatment.